2005
DOI: 10.1007/s11240-004-9157-1
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Hagenia abyssinica: a multipurpose tree

Abstract: An in vitro propagation protocol has been developed for Hagenia abyssinica using original material from both juvenile and mature trees. Juvenile explants were obtained from seedlings, as well as shoots and meristems from 5 to 7-month-old greenhouse grown plants. Shoots collected from stem bases of five genotypes were used to establish cultures from mature trees. Explants of seedling origin were used to optimize the multiplication medium and growth regulators concentration. The best result was obtained from sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
22
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 10 publications
9
22
0
1
Order By: Relevance
“…1e). Similar results have been reported in research on rooting of other species, for example Artemisia judaica (Liu et al, 2003) and Hagenia abyssinica (Feyissa et al, 2005). The presence of callus and inhibition of root growth may be associated with low survival of plants (Tab.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…1e). Similar results have been reported in research on rooting of other species, for example Artemisia judaica (Liu et al, 2003) and Hagenia abyssinica (Feyissa et al, 2005). The presence of callus and inhibition of root growth may be associated with low survival of plants (Tab.…”
Section: Resultssupporting
confidence: 86%
“…3). A similar two-step rooting procedure has been used successfully for different species (Martin, 2003;Feyissa et al, 2005;Siddique and Anis, 2007;Husain et al, 2008;Conde et al, 2008). IBA at high concentration is known to suppress root elongation (Korach et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were observed in explants of seedling from Hagenia abyssinica (Bruce J.F. Gmel), which presented either a similar in vitro growth, when cultivated in MS or WPM media (Feyissa et al, 2005). In contrast, plantlets of Punica granatum (L.) cultivated in WPM medium were apparently more vigorous and with longer shoots when compared with MS culture medium, which is an important feature in micropropagation (Valizadeh et al, 2013).…”
Section: Resultssupporting
confidence: 75%
“…In contrast, deleterious effect of combination of NAA with BA was also reported in Artemisia judaica (Liu et al 2003) and Garcinia indica (Malik et al 2005). However, in Hagenia abyssinica (Feyissa et al 2005), the best combination was observed on a medium containing BA and IBA, whereas IAA and BA combination was the optimum in Chonemorpha grandiflora (Nishitha et al 2006). Almost similar response was observed with BA and IBA or NAA combination in case of Pogostemon heyneanus (Hembrom et al 2006).…”
Section: Discussionmentioning
confidence: 66%